Design and synthesis of high-energy-density heterostructure Na0.7MnO2–Li4Mn5O12 cathode material for advanced lithium batteries. (31st October 2022) - Gu, Xiujuan; Cai, Yanjun; Yao, Xiang; Tian, Hualing; Su, Zhi
Abstract : The construction of the heterostructure, 0.6Na0.7 MnO2 –0.4Li4 Mn5 O12, can form a synergistic effect, which exhibits superior high-rate capability and excellent cycle performance. Abstract : The heterostructures, x Na0.7 MnO2 – y Li4 Mn5 O12 (0 < x < 1, 0 < y ≤ 1), were synthesized by a solid-phase method. X-Ray diffraction (XRD) analyses revealed that the as-prepared samples were heterostructures Na0.7 MnO2 and Li4 Mn5 O12 . Electron microscopy was used to study the lattice fingerprint area of 0.6Na0.7 MnO2 –0.4Li4 Mn5 O12 that showed (111) crystal surface of Li4 Mn5 O12 and (002) crystal surface of Na0.7 MnO2 . With different molar ratios of lithium and sodium, Li4 Mn5 O12 and Na0.7 MnO2 in the formed heterostructure will change accordingly, during the synthesis process. The XPS data also showed that Mn 3+ /Mn 4+ in the materials presented different ratios. The heterostructure, 0.6Na0.7 MnO2 –0.4Li4 Mn5 O12, exhibits superior high-rate capability and excellent cycle performance. The rate discharge capacity of 0.6Na0.7 MnO2 –0.4Li4 Mn5 O12 was maintained at 163.25 mA h g −1 at 500 mA g −1 . When cycled at 100 mA g −1, the discharge capacity was maintained at 189.80 mA h g −1 after 50 cycles. The construction of heterostructure can take the advantage of the high capacity of the layered structure of Na0.7 MnO2 and the stable spinel structure of Li4 Mn5 O12, which can form a synergistic effect and improve the electrochemical performance of cathode materials.